Modelling and Control of seven DOF Ride Model Using Hybrid Controller Optimized By Particle Swarm Optimization - Amin, M.H.I.; Hudha, K.; Amer, N.H.; Abd Kadir, Z.; Faiz, A. (Journal of Engineering and Technology (JET), 2015)
In this study, a seven degree of freedom (DOF) ride model of armored vehicle is employed in control system to control the vehicle ride performance especially in body acceleration, body pitch acceleration and body roll acceleration due to extreme road profile and disturbance using Hybrid control structure optimized by Particle Swarm Optimization (PSO) algorithm. The seven DOF ride model parameters are obtained from CARSIM software by selecting heavy vehicle High Mobility Multipurpose Wheeled Vehicle (HMMWV) as benchmark. The performance of the Hybrid control structure without optimization were compared to the performance of a simple PID control structure and passive 7 DOF vehicle ride model. Lastly, the performance of Hybrid control structure without optimization were compared to the performance of Hybrid control structure optimized by PSO algorithm.